Investigation on tip clearance control for the high-pressure rotor of an uncooled vaneless counter-rotating turbine. (April 2021) - Zhao, Wei; Sui, Xiuming; Zhang, Kai; Wei, Zeming; Zhao, Qingjun
In order to develop a tip clearance control system for an uncooled vaneless counter-rotating turbine, tip clearance variation of its high pressure rotor blade at off-design conditions is analyzed. Aero-thermal interaction simulation is performed to predict the temperature and deformation of the solid blade. At operating conditions with rotating speeds greater than 60% design value and expansion ratios greater than 85% design value, the blade tip clearance height at leading edge remains unchanged when the expansion ratio decreases, meanwhile that at trailing edge decreased obviously. However, the tip clearance height variations at the leading edge and trailing edge are almost the same in a conventional subsonic turbine at such conditions. The cause is that the flow in the high-pressure rotor is choked at these conditions. The choked flow results in that the fluid and solid blade temperatures upstream of the throat are not affected by the back pressure and only those downstream of the throat increases with the back pressure. Consequently, the blade height at leading edge keeps constant, and that at trailing edge varies because of thermal expansion. To avoid the rubbing of the blade and case, the blade height at trailing edge is diminished by 30%. As a result, the blade tip clearance height at low speed operating conditions increases in axial direction. Such a design leads to a stronger tip leakage flow. More flow losses might be generated. Therefore, a casing cooling method is proposed to control the blade tip clearance height at leading edge and trailing edge respectively. The deformations of the casing with different mass flow rate of cooling air at design and off-design conditions are calculated. It shows that the blade tip clearance heights at leading edge and at trailing edge of the rotor can be well controlled with appropriate amount of cooling air.